Relationship between Notch Receptors and Hyperoxia-induced Lung Injury in Newborn Rats - 张谦慎 常立文 刘汉楚 客志惠 陈红兵 (Current medical science, 2005)
To investigate role of Notchl- 3 in hyperoxia-induced lung injury in newborn rat exposed to 85% O2, SD rat litters born on the 22th day were randomly divided into two groups: room air group and hyperoxia group. The animals were sacrificed 1, 4, 7, 10, 14 and 21 days after continued exposure to oxygen (n=40, oxygen>0.85) or room air (n=40). 6 rats each group were used to assess lung histological changes by HE staining and expression of Notch in lungs by immunohistoehemistry. Total RNA was extracted by Trizol reagent from frozen lung tissues. Notch mRNA were measured by reverse transcription polymerase chain reaction (RT-PCR). Our results showed that 7, 14 and 21 days after O2 exposure, hyperoxia group showed lung injury characterized by pulmonary edema, hemorrhage and lung development arrest. Positive staining for Notehl, Notch 2 in hyperoxia group was much lower than those in room air group at all time points (P<0.01, P<0.05), but compared with the controls, the hyperoxia group showed higher expression of Notch3 (P>0.05). Immunostained cells were typically airways epithelia, alveolar epithelial and inflammatory cells, and fibroblasts in hyperoxia group (P<0.01). Notch mRNA levels showed similar change as protein level (P<0.01). It is concluded that the prolonged exposure to 85 % O2 resulted in abnormal expression of Notch receptors, which might contribute to the pathogenesis of hyperoxia induced lung injury in newborn rats. The decreased inhibition of Notch1 might be one of theprotective reaction and major mechanisms for proliferation/differentiation of type Ⅱ alveolar epithelial cells. The up-regulation of Notch3 activity might result in the lung development arrest of the newborn rats.